2007
DOI: 10.1016/j.wear.2007.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Wear behaviour of uncoated and diamond coated Si3N4 tools under severe turning conditions

Abstract: Tribological problems and corrosion degradation have been recognized as essential risks for total joint replacements, especially for all-metal arthroplasty. Few studies have focused on the interactions between tribology and corrosion (tribocorrosion) for implant materials. This paper addresses the importance of understanding tribocorrosion and the evaluation of such materials in simulated biological environments. Due to the complex effect of proteins on tribocorrosion, which has been demonstrated in previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…There have been studies carried out on the wear behavior of diamond-coated tools, such as the studies conducted by Martinho et al [49,50] about the wear mechanism of diamond-coated Si 3 N 4 . The main wear mechanism reported in these studies was abrasive wear, accompanied by adhesive wear.…”
Section: Tool Wear Mechanismsmentioning
confidence: 99%
“…There have been studies carried out on the wear behavior of diamond-coated tools, such as the studies conducted by Martinho et al [49,50] about the wear mechanism of diamond-coated Si 3 N 4 . The main wear mechanism reported in these studies was abrasive wear, accompanied by adhesive wear.…”
Section: Tool Wear Mechanismsmentioning
confidence: 99%
“…In order to increase tool lifespan and boost productivity, carbide and nitride tools have been gaining more and more market share, with tungsten carbide being used very frequently. In addition to further snowballing the lifespan of tools and subjecting them to increasingly severe working conditions, inserts are further coated with the above-mentioned plasma techniques [4,5]. At the outset, the chemical vapor deposition (CVD) technique was heavily exploited in obtaining diamond coatings [6,7], but evolved into many other materials as diamond is not suitable for machining ferrous alloys.…”
Section: Introductionmentioning
confidence: 99%
“…It was possible to observe that coated tools suffered more adhesive wear than the uncoated inserts. Still regarding the coated Si 3 N 4 ceramic cutting tools, studies made on the wear mechanism of these tools coated with diamond were conducted [68,69], the authors observed the machining performance of coated and uncoated tools; it was found that the cutting force was higher during machining with diamond-coated tools, due to the surface roughness of the rake face. Additionally, the parameter that influenced these cutting forces the most was the feed rate, contributing more to the increase in cutting force than cutting speed.…”
Section: Tool Wear Mechanismsmentioning
confidence: 99%